Burkholderia pseudomallei produces 2-alkylquinolone derivatives important for host virulence and competition with bacteria that employ naphthoquinones for aerobic respiration - Mou, Sherry; Savchenko, Viktoriia; Filz, Verena; Böttcher, Thomas; DeShazer, David (Frontiers in Microbiology, 2024)
Melioidosis is caused by Burkholderia pseudomallei, an opportunistic Gram-negative pathogen that inhabits soil and water in tropical and subtropical regions. B. pseudomallei infections often occur following contact with contaminated water or soil or by inhalation of contaminated dust and water droplets. There is limited knowledge about how B. pseudomallei is able to survive in harsh environmental conditions and compete with the microbes that inhabit these niches. Previous research demonstrated that 3-methyl-2-alkylquinolones (MAQs), and their corresponding N-oxides (MAQNOs), are produced by B. pseudomallei and provide a competitive advantage when grown in the presence of Gram-positive bacteria. In this study, 39 Gramnegative environmental bacteria in the Pseudomonadota and Bacteroidota phyla were isolated and characterized. Intriguingly, B. pseudomallei inhibited 71% of bacteria in the phylum Bacteroidota in zone of inhibition and coculture competition assays, but no Pseudomonadota isolates were similarly inhibited. Transposon mutagenesis was utilized to identify B. pseudomallei genes required for the inhibition of Sphingobacterium sp. ST4, a representative member of the Bacteroidota. Three mutations mapped to hmqA-G, the locus encoding 2alkylquinolone derivatives, and two mutations were identified in scmR, a gene encoding a quorum-sensing controlled LysR-type transcriptional regulator. B. pseudomallei strains with deletion mutations in hmqD and scmR were unable to produce 2-alkylquinolone derivatives or inhibit Bacteroidota isolates in competition assays. RAW264.7 murine macrophage cells were infected with B. pseudomallei 1026b and 1026b ∆hmqD and there was a 94-fold reduction in the number of intracellular 1026b ∆hmqD bacteria relative to 1026b. The 50% lethal dose (LD50) of 1026b and 1026b ∆hmqD in BALB/c mice was determined to be 3 x 10 5 colony forming units (CFU) and >1 x 10 6 CFU, respectively. Taken together, the results indicate that the products of the B. pseudomallei hmqA-G locus are important for intracellular replication in murine macrophages, virulence in a mouse model of melioidosis, and competition with bacteria that utilize naphthoquinones for aerobic respiration.